Platelets, Thromboinflammation and Neurovascular Disease - Sun, Ying; Langer, Harald F. (Frontiers in Immunology, 2022)
The brain and spinal cord are immune-privileged organs, but in the disease state protection mechanisms such as the blood brain barrier (BBB) are ineffective or overcome by pathological processes. In neuroinflammatory diseases, microglia cells and other resident immune cells contribute to local vascular inflammation and potentially a systemic inflammatory response taking place in parallel. Microglia cells interact with other cells impacting on the integrity of the BBB and propagate the inflammatory response through the release of inflammatory signals. Here, we discuss the activation and response mechanisms of innate and adaptive immune processes in response to neuroinflammation. Furthermore, the clinical importance of neuroinflammatory mediators and a potential translational relevance of involved mechanisms are addressed also with focus on non-classical immune cells including microglia cells or platelets. As illustrative examples, novel agents such as Anfibatide or Revacept, which result in reduced recruitment and activation of platelets, a subsequently blunted activation of the coagulation cascade and further inflammatory process, demonstrating that mechanisms of neuroinflammation and thrombosis are interconnected and should be further subject to in depth clinical and basic research.